Morphology of the Atlantic salmon (Salmo salar) tongue. (7th May 2020) - Abbate, Francesco; Guerrera, Maria Cristina; Levanti, Maria; Laurà, Rosaria; Germanà, Germana Patrizia; Montalbano, Giuseppe; Cavallaro, Mauro; Germanà, Antonino
Abstract: The Atlantic salmon ( Salmo salar ) is a freshwater and marine fish of the family Salmonidae, widely farmed in aquaculture facilities in several countries. The salmon are carnivorous, but in aquaculture, alternative foods have been experienced. It is well known that feeding in captivity should cause adaptation and modifications of the morphological characteristics of the oral cavity, especially of tongue; therefore, the aim of this study was to investigate, by light, laser confocal and scanning electron microscopy, the morphological characteristics of the tongue dorsal surface, considering the importance of the correlations between feeding habits and the anatomy of the tongue. Scanning electron microscopy demonstrates the presence of caniniform teeth with oro‐aboral orientation surrounded by numerous filiform papillae, single, fused or arranged in row. Oro‐aborally, the papillae show an appearance like a rosette and they disappear at level of the root. Light and laser confocal microscopy demonstrates that the mucosa is covered by a non‐keratinized stratified pavement epithelium with, in the deepest layer, the presence of a triangular structure whose apex is cranially directed and base facing aborally. In this structure, spindle‐shaped cells are present, with a vimentin immunoreactivity, that for their characteristics could be adult mesenchymal stem cells. The obtained data could be useful not only for further studies on the nutrition, but it is interesting the detection of tissues typical of the embryo‐fetal phase in the adult specimens tongue, thus giving a basis for studies of potential applications, if any, regarding cell therapies for different clinical indications.